Race, Memory and the Apartheid Archive
XVIII, 368 p.
Keywords: Race, Memory and the Apartheid Archive: Towards a Transformative Psychosocial Praxis draws on a psychosocial approach that is uniquely suited to the socio-historical and psychical analysis of racism. The book relies mainly on the memories, stories and narratives of ordinary people living in apartheid South Africa.